Legal Analysis of Criminal Responsibility of Perpetrators of Theft Crimes (Study of Decision Number: 662/Pid.B/2024/PN Jkt.Pst) - Makmaker, Petronela Yosinta Kelyombar; Hafidz, Jawade (Jurnal Hukum Khaira Ummah, 2025)
This study entitled "Legal Analysis of Criminal Liability of Perpetrators of Theft Crimes (Study of Decision Number: 662/Pid.B/2024/PN Jkt.Pst)" aims to analyze how criminal liability of perpetrators of theft crimes is determined in the Indonesian legal system and to determine the judge's considerations in identifying criminal acts based on the decision. The research method used in this study is the normative legal method, namely research that starts from applicable legal norms, with a case study approach to Decision Number 662/Pid.B/2024/PN Jkt.Pst as the object of study. The results of the study indicate that criminal liability is regulated through stages of proving the elements of a crime according to the Criminal Code, with a focus on proving unlawful acts, elements of error, and causality. In addition, the panel of judges considers strong evidence as well as social and moral aspects in making a decision. This study provides an overview of the importance of complete proof and consideration of moral values in enforcing criminal law on theft in Indonesia.